2009
DOI: 10.1136/jnnp.2008.165357
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance of drain associated meningitis/ventriculitis in a neurosurgery and neurological intensive care unit

Abstract: Objectives: There are currently no data available on drain associated infection occurrence related to the number of drainage days (DD), and thus drain associated infection rates. Therefore, a prospective surveillance study was conducted to determine drain associated infection rates and DD of hospital acquired external ventricular drain (EVD) and lumbar drain (LD) associated meningitis/ ventriculitis in a neurosurgery and a neurological intensive care unit. Methods: All patients admitted in 2005 and 2006 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 40 publications
8
63
4
1
Order By: Relevance
“…The study by Mayhall et al established a higher incidence of ventriculitis when EVDs were inserted for more than 5 days [11]. One of the studies, performed by Scheithauer et al, denied any correlation between the duration of the drainage and the incidence of infection [19]. The correlation between the duration of EVD replacements and the incidence of an EVD-associated infection was well established in our research.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The study by Mayhall et al established a higher incidence of ventriculitis when EVDs were inserted for more than 5 days [11]. One of the studies, performed by Scheithauer et al, denied any correlation between the duration of the drainage and the incidence of infection [19]. The correlation between the duration of EVD replacements and the incidence of an EVD-associated infection was well established in our research.…”
Section: Discussionsupporting
confidence: 55%
“…In one of the study it was demonstrated that hemorrhagic CSF -as a consequence of SAH or intraventricular hemorrhage (IVH) -occurred four times more frequently with a group of infected patients compared to the non-infected group [15]. Additionally the potential effect of SAH and IVH on the infection rate was mentioned in some of the later studies [7,[16][17][18][19]. Within our study the correlation between SAH and higher incidence of infections proved to be significant.…”
Section: Discussionmentioning
confidence: 61%
“…With six (10 %) confirmed and five (8 %) probable infections, the overall infection rate was comparable with previous published data [3,4,6,8,9,11].…”
Section: Discussionsupporting
confidence: 79%
“…Perioperative complications, however, such as infections, intracranial hemorrhages (ICHs), or catheter malplacements are well known [3,4]. Several previous trials have focused on catheter related cerebrospinal fluid infections (CSF) and bacterial colonization due to different types of EVDs (0-27 %), [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However in our study we have only labeled those patients who had a positive CSF culture along with clinical symptoms i.e. we have only taken into consideration the fi rst criterion in defi ning EVD-related infection.…”
Section: Methodsmentioning
confidence: 99%